Thyroid hormones induce doxorubicin chemosensitivity through enzymes involved in chemotherapy metabolism in lymphoma T cells - Díaz Flaqué, María Celeste (2019)
Thyroid hormones (THs) 3,3′,5-triiodo-L-thyronine (T3) and L-thyroxine (T4) are important regulators of the metabolism and physiology of most normal tissues.Cytochrome P450 family 3A members are drug metabolizing enzymes involved in theactivation and detoxification of several drugs. CYP3A4 is the major enzyme involvedin the metabolism of chemotherapeutic drugs. In this work, we demonstrate thatTHs induce a significant increase in CYP3A4 mRNA levels, protein expression andmetabolic activity through the membrane receptor integrin αvβ3 and the activation ofsignalling pathways through Stat1 and NF-κB. We reasoned that TH-induced CYP3A4modulation may act as an important regulator in the metabolism of doxorubicin(Doxo). Experiments in vitro demonstrated that in CYP3A4-knocked down cells, noTH-mediated chemosensitivity to Doxo was observed. We also found that THs modulatethese functions by activating the membrane receptor integrin αvβ3. In addition, weshowed that the thyroid status can modulate CYP450 mRNA levels in tumor and livertissues, and the tumor volume in response to chemotherapy in vivo. In fact, Doxotreatment in hypothyroid mice was associated with lower tumors, displaying lowerlevels of CYP enzymes, than euthyroid mice. However, higher mRNA levels of CYPenzymes were found in livers from Doxo treated hypothyroid mice respect to control.These results present a new mechanism by which TH could modulate chemotherapyresponse. These findings highlight the importance of evaluating thyroid status inpatients during application of T-cell lymphoma therapeutic regimens.